Plato is not Platonism: Musings on the Derivative De-eroticized Nature of the Modern Subject - Sena, Marylou (Bollettino Filosofico, 2018)
One of the enduring problems of phenomenology concerns the dispute over the nature of the modern subject (subjectivity) that is responsible for its own agnostic and atheistic views of the world. In an effort to understand the “obscurity” around the nature of the modern subject, Heidegger turns to Plato (1936-37) bearing in mind Nietzsche’s distinction between Plato and Modern Platonism. From the perspective of Plato’s eroticized conception of the logos, based as it is in the soul’s form of sophrosyne, Heidegger draws the following conclusion: the Kantian claim of Modern Platonism that the nonsensuous being of Plato’s Ideas and of the gods cannot in principle be known is based on a de-eroticized, derivative, conception of the logos. But Heidegger fails to see Plato’s own astonishing account of how this new logos of the “non-lover” is based in a derivative form of sophrosyne.